2023
DOI: 10.3390/pr11113253
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Methods Change Nitrogen Distribution and Enzyme Activities in Maize Rhizosphere and Non-Rhizosphere Chernozem in Jilin Province of China

Ning Huang,
Xingmin Zhao,
Xinxin Guo
et al.

Abstract: The tillage method in farming systems is essential to develop strategies to increase fertilizer uptake by plant roots and to avoid environmental pollution. The field study aimed to investigate the characteristics of nitrogen and enzyme activities in rhizosphere soil with different tillage methods. Four treatment plots applied with fertilizers were established: continuous rotary tillage (CR), plowing-rotary tillage (PR), continuous no-till (CN) and ploughing-no-till (PN). The total content of nitrogen in cherno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Previous studies have shown that SOC content and soil nutrient availability are reduced as soil depth increases, accompanied by changes in microbial biomass and activity [15]. Zhao [6] and Yang et al [7] reported that inversion tillage increases soil microbial biomass and improves soil enzymatic activities, which is consistent with our results. The soil pore structure and index of richness in the 15-35 cm layer were improved in this study (Tables 1 and 2; Figure 4), which suggests that inversion tillage can reduce soil physical restrictions and further homogenize the whole cultivated horizon, further increase soil nutrient availability, and enhance microbial biomass and activity [15].…”
Section: Effects Of Incorporation Of Inversion Tillage and Organic Fe...supporting
confidence: 92%
See 3 more Smart Citations
“…Previous studies have shown that SOC content and soil nutrient availability are reduced as soil depth increases, accompanied by changes in microbial biomass and activity [15]. Zhao [6] and Yang et al [7] reported that inversion tillage increases soil microbial biomass and improves soil enzymatic activities, which is consistent with our results. The soil pore structure and index of richness in the 15-35 cm layer were improved in this study (Tables 1 and 2; Figure 4), which suggests that inversion tillage can reduce soil physical restrictions and further homogenize the whole cultivated horizon, further increase soil nutrient availability, and enhance microbial biomass and activity [15].…”
Section: Effects Of Incorporation Of Inversion Tillage and Organic Fe...supporting
confidence: 92%
“…Inversion tillage and organic fertilizer application showed positive effects on maize yields (Figure 3), contributing mainly to the improvements in soil nutrients and physical properties [5,6,29]. In our study, T35+M treatment resulted in a higher maize yield than other treatments, which can be explained by the fact that the 15-35 cm layers under T15 treatment dramatically limited deep root growth and development and thus restricted the utilization of soil nutrients by the crop in subsoil [33][34][35].…”
Section: Effects Of Soil Properties and Microbial Resource Limitation...mentioning
confidence: 52%
See 2 more Smart Citations
“…Nevertheless, compounded by the predominance of small-scale farming, where tillage is often carried out using smaller machinery, forage maize productivity was often constrained by shallow tillage layers, compacted soil layers, and low nutrient uptake [13]. Prior research underscores the detrimental impact of traditional tillage practices on soil quality and crop development, exacerbating drought susceptibility and impeding yield stability and the growth of forage maize in northwest China [14,15].…”
Section: Introductionmentioning
confidence: 99%